2012
DOI: 10.1071/en12132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hydrophobicity parameters of perfluorinated alkylated substances from reversed-phase high-performance liquid chromatography

Abstract: Environmental context. Perfluorinated compounds are synthetic chemicals shown to be present in the blood of humans. To study how these contaminants get into our blood requires a good understanding of their physicochemical properties. We describe an alternative way to obtain values for how perfluorinated compounds distribute between water and fatty phases (mimicking e.g. gut content and gut wall), which is essential information for modelling and understanding the environmental fate of these chemicals.Abstract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Medium‐chain perfluorocarboxylic acids (PFPeA to PFHpA) exhibited reduced accumulation, generating a U‐shaped trend between perfluoroalkyl chain length and RCF (Figure A). Long‐chain perfluorocarboxylic acids and all 3 perfluorosulfonic acids exhibited a linear relationship with the literature derived experimental sorption coefficient , k 0 (Figure C,D); however, PFBA and PFPeA show a much higher affinity for roots than predicted by k 0 . The perfluorocarboxylic acid SCFs show a similar U‐shaped trend with chain length, but because shoot concentrations do not reach saturation (Figure ), the values represent only the time point at which they were collected.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Medium‐chain perfluorocarboxylic acids (PFPeA to PFHpA) exhibited reduced accumulation, generating a U‐shaped trend between perfluoroalkyl chain length and RCF (Figure A). Long‐chain perfluorocarboxylic acids and all 3 perfluorosulfonic acids exhibited a linear relationship with the literature derived experimental sorption coefficient , k 0 (Figure C,D); however, PFBA and PFPeA show a much higher affinity for roots than predicted by k 0 . The perfluorocarboxylic acid SCFs show a similar U‐shaped trend with chain length, but because shoot concentrations do not reach saturation (Figure ), the values represent only the time point at which they were collected.…”
Section: Resultssupporting
confidence: 55%
“…, where C eq is concentration at equilibrium, and k 1 is uptake rate constant. b Depuration: Roots were fitted with a nonlinear fit: the literature derived experimental sorption coefficient [33], k 0 ( Figure 4C,D); however, PFBA and PFPeA show a much higher affinity for roots than predicted by k 0 . The perfluorocarboxylic acid SCFs show a similar U-shaped trend with chain length, but because shoot concentrations do not reach saturation (Figure 2), the values represent only the time point at which they were collected.…”
Section: Sncfsmentioning
confidence: 99%
“…This is the effect of 2 mechanisms: 1) the fluorine atoms in CF x moieties are larger than the hydrogen atoms in CH x moieties and thereby increase the cavity size and energy required for perfluoroalkyl carboxylates to dissolve in water compared with that of alkyl carboxylates , and 2) the highly electronegative fluorine atoms in the perfluoroalkyl chain maintain an electron‐withdrawing effect and tend to pull the negative charge away from the carboxylic head group, making it less hydrated and therefore reducing affinity with the aqueous phase . De Voogt et al found similar results for perfluoroalkyl carboxylates, but log k ′ 0 values increased more per carbon atom (0.66 vs 0.57 log unit per carbon atom in the present study; Supplemental Data, Table S2), resulting in lower log k ′ 0 values for perfluoroalkyl carboxylates with shorter chain lengths and higher log k ′ 0 values for longer chain lengths when compared with the present findings (Supplemental Data, Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…To measure the retention of test analytes on a C 18 phase, logarithmic capacity factors (log k ′) were calculated from the retention time of the target compound ( t r ) and that of an unretained compound ( t 0 ) logk=logtrt0t0 Because the retention of a hydrophobic compound on a C 18 phase in pure water as eluent can increase up to several hours, an organic modifier is added to the mobile phase to promote elution of the compounds. When methanol is used as an organic modifier, the relationship between the logarithmic capacity factor and the methanol fraction in the mobile phase is linear for most neutral solutes and can be expressed as logk=a×φ+logk0 where the slope a represents the change in the logarithmic capacity factor of the target compound as a function of the methanol fraction (normalφ) and the intercept (log k ′ 0 ) represents the logarithmic capacity factor at normalφ 0 (i.e., in pure water). A sufficient number of measurements have to be made at different modifier strengths before extrapolation to pure water can be applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation